Reducing anticipated non‐suicidal self‐injury by improving body esteem in individuals with weight suppression: A proof of concept study. Issue 2 (21st January 2019) - Kennedy, Grace A.; Jean Forney, Katherine; Pinner, Dennis; Martinez, Kimberly M.; Buchman‐Schmitt, Jennifer M.; Keel, Pamela K.
Abstract: Objective: Research suggests that weight suppression (WS) is linked to non‐suicidal self‐injury (NSSI) and that drive for thinness and depression may explain this association. We conducted a proof‐of‐concept study using a randomized control trial design to determine if improving body esteem and reducing depressive symptoms reduced NSSI in individuals with WS. Method: Weight suppressed participants ( N = 60) who engaged in NSSI were recruited from the community and randomly assigned to an on‐line intervention or control condition. The on‐line intervention was adapted from a cognitive‐dissonance intervention originally designed to reduce thin‐ideal internalization in females to an intervention to reduce internalization of unhealthy body ideals in both genders. Participants' weight/shape concerns, depressive symptoms, and NSSI were assessed at pre‐ and post‐intervention, or at baseline and 2‐week follow‐up for controls. Results: Compared to controls, participants in the treatment condition reported greater decreases in likelihood of future NSSI [Cohen's d (95% CI) = −0.38 (−0.90–0.15)], weight/shape concerns [−1.19 (−1.75 to −0.62)], depressive symptoms [−1.00 (−1.56 to −0.45)], and significant improvements in appearance [1.27 (0.70–1.84)] and weight esteem [1.38 (0.80–1.96)]. Discussion: Future work could test this intervention in a larger trial with an active alternative treatment condition.